Determinants of Privatization: Evidence from Pakistan - MUHAMMAD TAHIR KHAN (Journal of Business & Tourism, 2021)
Privatization is something that can take the ownership factor from state and give it to other and since form 1990’s it has turned out to be a most important for both the developing countries as well as for the developed countries. However, in this study we identify the determinants that can lead the government of Pakistan towards privatization by relying on the data that has been taken from privatization commission of Pakistan (PCP) and state bank of Pakistan database between the years 1991 to 2014. Our results identify that the decision for privatization has been initiated by external factor i.e international financing agencies and after that it has been shaped by internal factors that is basically due to economic condition.